Life-cycle civil engineering proceedings of the first International Symposium on Life-Cycle Civil Engineering, Varenna, Lake Como, Italy, June 10-14, 2008 - Biondini, Fabio; Frangopol, Dan M. (CRC Press, 2008)
Covers various aspects of life-cycle assessment, design, maintenance, rehabilitation, and monitoring of civil engineering systems. This work includes such topics as life-cycle damage processes, life-cycle assessment and design, life-cycle monitoring, maintenance and rehabilitation, and life-cycle performance of special structures.